Lophoranina maxima Beschin, Busulini, De Angeli & Tessier, 2004 (Decapoda Brachyura, Raninidae) from Lower Eocene laminites of the “Pesciara di Bolca” (Verona, northeast Italy) - Busulini, Alessandra; Zorzin, Roberto; Beschin, Claudio; Tessier, Giuliano (Geologija, 2020)
The sole specimen of a raninid crab found to date in the Lower Eocene Fossil-Lagerstätte of the “Pesciara di Bolca” (Verona, northeast Italy) and referred to Lophoranina maxima, is described. Results of a CT analysis of this specimen and of a study of its cuticle are discussed.